Integration of mural art in the residential architecture of Ricardo Carbonell - Avendaño, Ayansi (Realidad, Revista de Ciencias Sociales y Humanidades, 2017)
During architectural modernity in El Salvador, that had its peak between 1940 and 1980, took place a meeting between art and architecture. In this process, there was a particular case of integration of art into housing, that proposed by Ricardo Carbonell (1929), himself both an architect and artist. He made mural works in private houses and some public buildings. This article analyzes this experiment of integration by Ricardo Carbonell as a contribution to the enrichment of the identity of salvadoran architecture. His work is studied from three key aspects: first, the definition of architecture as art; second, to underline the conexions of concrete referents in the art-architecture movements in Latin America that were contemporary of Carbonell; and, third, a close examination of the work of Carbonell from the standpoing of his artistc influences, and his training in the context of architectural modernity. Realidad: Revista de Ciencias Sociales y Humanidades No. 150, 2017: 91-117